2010
DOI: 10.1002/hed.21567
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for T1–T2 squamous cell carcinomas of the mobile tongue: A retrospective cohort study

Abstract: This study corroborates several known prognostic factors and indicates that diagnosis of oral lichen planus may be a risk factor for disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
19
1
1
Order By: Relevance
“…Shim et al also found that, when compared to well‐differentiated tumors of the oral tongue, moderately or poorly differentiated tumors resulted in nearly a 7‐fold increased risk of mortality (HR = 6.93; p = 0.001). However, other studies have shown no survival impact of tumor grade or margin involvement . Our study findings are congruent with the latter studies in that tumor grade and margin involvement were not independent predictors of survival.…”
Section: Discussionsupporting
confidence: 89%
“…Shim et al also found that, when compared to well‐differentiated tumors of the oral tongue, moderately or poorly differentiated tumors resulted in nearly a 7‐fold increased risk of mortality (HR = 6.93; p = 0.001). However, other studies have shown no survival impact of tumor grade or margin involvement . Our study findings are congruent with the latter studies in that tumor grade and margin involvement were not independent predictors of survival.…”
Section: Discussionsupporting
confidence: 89%
“…Several adverse pathological features like increasing DOI, perineural invasion, and lympho‐vascular invasion have been implicated in poor outcomes in OSCC. Amongst these, the prognostic implications of DOI and tumour thickness in OSCC have been well‐reported . The major changes in AJCC eighth edition included the incorporation of DOI into the staging system and exclusion of extrinsic muscle involvement from T4 staging of tongue cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the composition of bacterial flora might also have a TLR5-dependent effect on cancer development. Oral tongue squamous cell carcinoma has low 5-year survival (Sano and Myers, 2007), but there are no clinically practical markers for risk assessment of OTSCC survival or recurrence (Bello et al , 2011; Bonnardot et al , 2011; Kim et al , 2011). Our study provides evidence for a relationship of TLR5 expression levels and prognosis in OTSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the recent advances in their treatment, the 5-year survival remains around 50% (Sano and Myers, 2007). Various molecular markers and factors have been proposed for risk assessment of OTSCC survival or recurrence, but none are currently in clinical use (Bello et al , 2011; Bonnardot et al , 2011; Kim et al , 2011). …”
mentioning
confidence: 99%